1986
DOI: 10.1093/jac/18.supplement_e.27
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial properties of imipenem with special reference to the activity against methicillin-resistant staphylococci, cefotaxime-resistant Enterobacteriaceae and Pseudomonas aeruginosa

Abstract: Imipenem was examined with standardized agar dilution procedures against a wide range of bacteria. Geometric mean MICs against the genera Escherichia, Klebsiella, Enterobacter, Citrobacter and Serratia were 0.1-0.4 mg/l, and Proteus and Providencia spp. were inhibited by 0.25-4 mg/l. Acinetobacter calcoaceticus var. anitratum strains were inhibited by concentrations ranging from 0.12-0.5 mg/l. Methicillin-susceptible staphylococci were highly susceptible to the drug (MICs: less than or equal to 0.03 mg/l) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Several investigators have shown that imipenem possesses an activity superior to previous (3-lactams against P. aeruginosa, in cluding strains resistant to third-generation ce phalosporins [4,5]. The narrow range of the MICs of imipenem against our P. aeruginosa strains is comparable to that reported by other investigators.…”
Section: Discussionsupporting
confidence: 81%
“…Several investigators have shown that imipenem possesses an activity superior to previous (3-lactams against P. aeruginosa, in cluding strains resistant to third-generation ce phalosporins [4,5]. The narrow range of the MICs of imipenem against our P. aeruginosa strains is comparable to that reported by other investigators.…”
Section: Discussionsupporting
confidence: 81%
“…1) is a recent penem anti biotic available for intravenous adminis tration [1,2], The objective of the present study is to compare the activity of ALP 201 with other relevant antibacterial com pounds against gram-negative rods and gram-positive cocci [3,4], C 0 2Na , USA.…”
Section: Introductionmentioning
confidence: 99%